After innocence - Joyce, Brenda; Copyright Paperback Collection (Library of Congress) (New York, N.Y Avon Books, 1994)
Estranged from society after an accident leaves her with a limp, beautiful artist Sofie O'Neill finds solace in her private world of painting, until the arrival of dashing diamond smuggler Edward Delanza awakens Sofie to a passionate new world
1
Keywords: Historical fiction; Love stories